Smart Glove Sebagai Alat Bantu Komunikasi Pasien - Gilang Wiranda; Agus Urip A Agus Urip A; Putri Madona (Jurnal Komputer Terapan, 2023)
Therapeutic communication in nursing is the process of communication conducted by a nurse while carrying out nursing interventions, with the aim of providing therapeutic benefits in the patient's healing process. In therapeutic communication, a nurse can gain a deep understanding of the condition of the patient being treated and decide on the most appropriate nursing actions. This is to ensure that the care provided is tailored to the patient's needs, thereby helping to expedite the healing process. A nurse-call device, also known as "nurse-call," is one of the common devices used in hospitals as a means of communication between patients and nurses. This device plays a vital role in delivering optimal nursing care, especially when patients require immediate assistance. In the context of this research, a Smart Glove device is proposed that allows patients to communicate with nurses when they have various needs during the care process. The developed system was then tested using functionality and performance testing methods. The performance testing results showed a minimal error rate of 14%, while functionality testing indicated that the sensors worked well, with an average latency of approximately 9.53ms.